Efficacy and safety of baricitinib in hospitalized adults with severe or critical COVID-19 (Bari-SolidAct): a randomised, double-blind, placebo-controlled phase 3 trial - Trøseid, Marius; Arribas, José R; Assoumou, Lambert; Holten, Aleksander Rygh; Poissy, Julien; Terzić, Vida; Mazzaferri, Fulvia; Baño, Jesús Rodríguez; Eustace, Joe; Hites, Maya; Joannidis, Michael; Paiva, José-Artur; et al. (Critical care, 2023)
BACKGROUND: Baricitinib has shown efficacy in hospitalized patients with COVID-19, but no placebo-controlled trials have focused specifically on severe/critical COVID, including vaccinated participants. METHODS: Bari-SolidAct is a phase-3, multicentre, randomised, double-blind, placebo-controlled trial, enrolling participants from June 3, 2021 to March 7, 2022, stopped prematurely for external evidence. Patients with severe/critical COVID-19 were randomised to Baricitinib 4 mg once daily or placebo, added to standard of care. The primary endpoint was all-cause mortality within 60 days. Participants were remotely followed to day 90 for safety and patient related outcome measures. RESULTS: Two hundred ninety-nine patients were screened, 284 randomised, and 275 received study drug or placebo and were included in the modified intent-to-treat analyses (139 receiving baricitinib and 136 placebo). Median age was 60 (IQR 49-69) years, 77% were male and 35% had received at least one dose of SARS-CoV2 vaccine. There were 21 deaths at day 60 in each group, 15.1% in the baricitinib group and 15.4% in the placebo group (adjusted absolute difference and 95% CI - 0.1% [- 8·3 to 8·0]). In sensitivity analysis censoring observations after drug discontinuation or rescue therapy (tocilizumab/increased steroid dose), proportions of death were 5.8% versus 8.8% (- 3.2% [- 9.0 to 2.7]), respectively. There were 148 serious adverse events in 46 participants (33.1%) receiving baricitinib and 155 in 51 participants (37.5%) receiving placebo. In subgroup analyses, there was a potential interaction between vaccination status and treatment allocation on 60-day mortality. In a subsequent post hoc analysis there was a significant interaction between vaccination status and treatment allocation on the occurrence of serious adverse events, with more respiratory complications and severe infections in vaccinated participants treated with baricitinib. Vaccinated participants were on average 11 years older, with more comorbidities. CONCLUSION: This clinical trial was prematurely stopped for external evidence and therefore underpowered to conclude on a potential survival benefit of baricitinib in severe/critical COVID-19. We observed a possible safety signal in vaccinated participants, who were older with more comorbidities. Although based on a post-hoc analysis, these findings warrant further investigation in other trials and real-world studies. Trial registration Bari-SolidAct is registered at NCT04891133 (registered May 18, 2021) and EUClinicalTrials.eu ( 2022-500385-99-00 ).
Keywords: dospělí; farmakoterapie COVID-19; RNA, Viral; RNA virová; lidé středního věku; lidé; Female; dvojitá slepá metoda; mužské pohlaví; SARS-CoV-2; Double-Blind Method; Male; COVID-19 Drug Treatment; Middle Aged; Adult; COVID-19; ženské pohlaví; Humans